CO2 wettability of seal and reservoir rocks and the implications for carbon geo‐sequestration. Issue 1 (20th January 2015) - Iglauer, Stefan; Pentland, C. H.; Busch, A.
Abstract: We review the literature data published on the topic of CO2 wettability of storage and seal rocks. We first introduce the concept of wettability and explain why it is important in the context of carbon geo‐sequestration (CGS) projects, and review how it is measured. This is done to raise awareness of this parameter in the CGS community, which, as we show later on in this text, may have a dramatic impact on structural and residual trapping of CO2 . These two trapping mechanisms would be severely and negatively affected in case of CO2 ‐wet storage and/or seal rock. Overall, at the current state of the art, a substantial amount of work has been completed, and we find that: Sandstone and limestone, plus pure minerals such as quartz, calcite, feldspar, and mica are strongly water wet in a CO2 ‐water system. Oil‐wet limestone, oil‐wet quartz, or coal is intermediate wet or CO2 wet in a CO2 ‐water system. The contact angle alone is insufficient for predicting capillary pressures in reservoir or seal rocks. The current contact angle data have a large uncertainty. Solid theoretical understanding on a molecular level of rock‐CO2 ‐brine interactions is currently limited. In an ideal scenario, all seal and storage rocks in CGS formations are tested for their CO2 wettability. Achieving representative subsurface conditions (especially in terms of the rock surface) in the laboratory is of key importance but also very challenging. Key Points: CO2 wettability of seal and storage rock: summary of state‐of‐the‐art CO2 wettability of rocks Impact on residual and structural trapping capacity